The Effects of “Dance with fruits” analogy in alleviating alternative conceptions in Acids and Bases [Case study of Grade 11 Physical Sciences]: The effects of “Dance with fruits” analogy in alleviating alternative conceptions in Acids and Bases[Case study of Grade 11 Physical Sciences] - Chinaka, Taurayi WIllard (Journal of Turkish Science Education, 2021)
The effects of “Dance with fruits” analogy in alleviating alternative conceptions in Acids and Bases[Case study of Grade 11 Physical Sciences]  This study investigated the effects of the “dance with fruits” analogy on students’ alleviation of alternative conceptions among physical sciences high school students in one of the province in South Africa. The study used a sequential mixed method research design consisting of quasi-experimental control group pre-test, post-test and semi-structured interviews. The target population of this study was all grade 11 physical science students in all 11 districts of the province. Accessible population included 4 schools in the district close to the researcher. The participants of this study were 117 physical sciences grade 11 students. A research instrument Acid and Base Alternative conception Test (ABACT) was administered twice as a pre-and post-test to both control and experiment groups. Analysis of pre and post-tests suggested that students strongly held an alternative conception that the strength of acid is related to its concentration and corrosiveness. Molecular drawings of acids and base dissociations revealed notable patterns on how the distribution and ratio of molecules/ions in aqueous solutions are perceived.The results also indicated that the participants in the experimental groups had fewer alternative conceptions as compared to the control groups. The implication of this study for science educators is that correct use of analogies can assist students’ understanding of abstract concepts about acids and bases.
Keywords: Analogy; Acid and Base; Structure-mapping theory; PH; Conductivity; base and target domains